Characterization of anopheline (Diptera: Culicidae) larval habitats in Nouakchott, Mauritania - O. Ahmedou Salem Mohamed Salem; M. Lekweiry Khadijetou; M. Hasni Moina; Konate Lassana; Briolant Sébastien; Faye Ousmane; O. Mohamed Salem Boukhary Ali (Journal of Vector Borne Diseases, 2013)
Background & objectives: Despite the increasing number of reported autochthonous malaria cases in Nouakchott and the identification of Anopheles arabiensis as the major malaria vector in this Saharan city, anopheline larval habitats have never been identified so far. The objective of this study was to identify and characterize anopheline larval habitats in Nouakchott. Methods: During September and October 2012, samples from pools of rainwater, water discharged from standpipes and household drinking water tanks in the districts of Dar Naim, Teyarett and Arafat were analyzed for the presence/absence of anopheline larvae and physicochemical characterization of breeding habitats. Results: Of the 51 prospected water bodies, eight consisting of seven water discharged from standpipes and one household drinking water tank were productive for Anopheles sp. All emerged anopheline mosquitoes from the positive dipping were morphologically identified as members of the An. gambiae complex. Multivariate regression analyses showed that a salinity up to 0.1 g/l and a shaded situation were respectively protective factors against high larval density in breeding sites (adjusted odds ratio = 0.62, 95% CI [0.44-0.87], p = 0.0052 and adjusted odds ratio = 0.56, 95% CI [0.44-0.71, p <0.0001] and a pH up to 7.61 was a risk factor for high larval density in breeding sites (adjusted odds ratio = 1.56, 95% CI [1.25-1.95], p = 0.0001). Interpretation & conclusion: The study demonstrated in Nouakchott that despite an arid and dry climate, human practices have contributed to the establishment of favourable environmental conditions for the development of anopheline mosquitoes and, therefore, maintaining malaria transmission in this Saharan city. The core malaria vector control intervention as the use of long-lasting insecicidal nets (LLINs) could be complemented in Nouakchott by larval source control. In this area, appropriate larval control measures may be recommended in line with an integrated vector management (IVM) approach.